2021
DOI: 10.3390/biom11121813
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology and Treatment of Essential Tremor: The Role of Adenosine and Dopamine Receptors in Animal Models

Abstract: Essential tremor (ET) is one of the most common neurological disorders that often affects people in the prime of their lives, leading to a significant reduction in their quality of life, gradually making them unable to independently perform the simplest activities. Here we show that current ET pharmacotherapy often does not sufficiently alleviate disease symptoms and is completely ineffective in more than 30% of patients. At present, deep brain stimulation of the motor thalamus is the most effective ET treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 267 publications
(391 reference statements)
1
34
0
Order By: Relevance
“…We previously demonstrated that electrical lesion of IO suppressed nicotine-induced tremor ( Kunisawa et al, 2016 ). Consistent with the fact that IO is closely involved in the pathogenesis of essential tremor in humans ( Puschmann and Wszolek, 2011 ; Kosmowska and Wardas, 2021 ; Welton et al, 2021 ), our results suggest that the IO-cerebellar system plays a crucial role in the generation of nicotine-induced kinetic tremor. IO receives dopaminergic innervation from the ventral tegmental and prerubral parafascicular areas ( Fallon et al, 1984 ; Toonen et al, 1998 ; Kitahama et al, 2000 ), suggesting a potential role of dopaminergic neurons in modulating tremor induction.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We previously demonstrated that electrical lesion of IO suppressed nicotine-induced tremor ( Kunisawa et al, 2016 ). Consistent with the fact that IO is closely involved in the pathogenesis of essential tremor in humans ( Puschmann and Wszolek, 2011 ; Kosmowska and Wardas, 2021 ; Welton et al, 2021 ), our results suggest that the IO-cerebellar system plays a crucial role in the generation of nicotine-induced kinetic tremor. IO receives dopaminergic innervation from the ventral tegmental and prerubral parafascicular areas ( Fallon et al, 1984 ; Toonen et al, 1998 ; Kitahama et al, 2000 ), suggesting a potential role of dopaminergic neurons in modulating tremor induction.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, electrical lesion of IO suppressed the induction of nicotine tremor, illustrating that nicotine induces kinetic tremor by activating IO neurons. Since excitation of the olivo-cerebellar neural pathway is reportedly involved in generation of essential tremor in humans ( Puschmann and Wszolek, 2011 ; Kosmowska and Wardas, 2021 ; Welton et al, 2021 ), our findings suggest that nicotine-induced tremor has the same neural basis as essential tremor. In fact, nicotine tremor was significantly alleviated by drugs effective for human essential tremor (e.g., propranolol, diazepam, and phenobarbital), but was unaffected by medications for Parkinson’s disease tremor (i.e., trihexyphenidyl) ( Kunisawa et al, 2018 ).…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations